IMPROVING COMPETITIVENESS THROUGH MAKING SIMPLE CASH BOOKS FOR BUSINESS TAILOR AND MIE REBUS / SATE - Nurzaimah; Ismail, Mutia; Indra, Naleni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Devotion is done in Medan City and Lubuk Pakam,Sumatera Utara Province. Devotion takes the title "Training of Simple Cash Book Compilation for Multiple Small Medium Enterprises (SMEs)". Devotion to this community will be done for two householders from the preliminary survey who know that the housewives who do business behind this is the ability to perform activities that do not exist or simple cash bookkeeping do not know yet. The Community Service team will endeavor to assist the business partner on the basis of the difficulties it faces. Creating a better business. The target of mono community service activity this year is expected to develop business partner efforts that had been only staying at home so that will try to open the business of boiled noodles / satay then to sew can develop the seams. Many people will sew in their place.